Identification of patients' spiritual needs using a spiritual health assessment tool - Green, Cheryl Ann (Creating Healthy Work Environments, 2019)
Citation Key Alias: lens.org/090-145-772-380-333 tex.type: [object Object]
Keywords: dept.nur; ⛔ No DOI found

Workplace incivility: Nurse leaders as change agents - Green, Cheryl Ann (Nursing Management, 2019)
An abstract is unavailable.
7 citations (Crossref) [2023-10-31]
Keywords: Humans; Interprofessional Relations; Leadership; Nursing Staff; Organizational Innovation; Workplace; dept.nur; human; leadership; nursing staff; organization; peer-reviewed; public relations; workplace